2019
DOI: 10.1007/s40273-019-00792-7
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab for Treating Relapsed or Refractory Classical Hodgkin Lymphoma: An Evidence Review Group Perspective of a NICE Single Technology Appraisal

Abstract: As part of its Single Technology Appraisal (STA) process, the National Institute for Health and Care Excellence (NICE) invited the manufacturer (Merck Sharp & Dohme; MSD) of pembrolizumab (Keytruda ® ) to submit evidence of its clinical and cost effectiveness for the treatment of patients with relapsed or refractory classical Hodgkin lymphoma (RRcHL) who did not respond to treatment with brentuximab vedotin. Kleijnen Systematic Reviews Ltd, in collaboration with Maastricht University Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The patient presented here has failed the first-line treatment of antibody-drug conjugate therapy as well as the salvage therapy since new legions have developed, as shown in the PET scan. It has been demonstrated that unresponsive adult patients to at least one line of chemotherapy and/or salvage therapy are candidates for pembrolizumab (a PD-1 inhibitor) preceding ASCT [30]. Therefore, in line with the previous study, the patient in this report was started on immune-engage therapy (pembrolizumab), which successfully resolved the previous pelvis and abdominal lymph nodes.…”
Section: Discussionsupporting
confidence: 57%
“…The patient presented here has failed the first-line treatment of antibody-drug conjugate therapy as well as the salvage therapy since new legions have developed, as shown in the PET scan. It has been demonstrated that unresponsive adult patients to at least one line of chemotherapy and/or salvage therapy are candidates for pembrolizumab (a PD-1 inhibitor) preceding ASCT [30]. Therefore, in line with the previous study, the patient in this report was started on immune-engage therapy (pembrolizumab), which successfully resolved the previous pelvis and abdominal lymph nodes.…”
Section: Discussionsupporting
confidence: 57%
“…On the other hand, there may be comparators that only become relevant after the final scope has been issued. As highlighted by Grimm et al [ 22 ], it is important to also include the possibility of addition of comparators under appraisal at the time.…”
Section: Key Methodological Issuesmentioning
confidence: 99%
“…[38] However, in relapse/refractory Hodgkin's disease it was found similarly useful as Nivolumab and has been approved by FDA for the use. [39] This drug has been associated with various hematological disorders like TTP (Thrombotic Thrombocytopenic Purpura) and autoimmune hemolytic anemia.…”
Section: Nivolumab (Opdivo R )mentioning
confidence: 99%